Relationship between interRAI HC and the ICF: opportunity for operationalizing the ICF - Ljunggren Gunnar; Ikegami Naoki; Hirdes John; Henrard Jean; Gray Len; Finne-Soveri Harriet; Berg Katherine; Morris John N; Paquay Louis; Resnik Linda; Teare Gary (BMC, 2009)
Abstract Background The International Classification of Functioning, Disability and Health (ICF) is embraced as a framework to conceptualize human functioning and disability. Health professionals choose measures to represent the domains of the framework. The ICF coding classification is an administrative system but multiple studies have linked diverse clinical assessments to ICF codes. InterRAI-HC (home care) is an assessment designed to assist planning of care for patients receiving home care. Examining the relationship between the ICF and the interRAI HC is of particular interest because the interRAI assessments are widely used in clinical practice and research, are computerized, and uploaded to databases that serve multiple purposes including public reporting of quality in Canada and internationally. The objective of this study was to examine the relationship between the interRAI HC (home care) assessment and the ICF. Specifically, the goal was to determine the proportion of interRAI HC items that can be linked to each of the major domains of the ICF (Body Function, Body Structure, Activities and Participation, and the Environmental Factors), the chapters and the specific ICF codes. Methods Three coders who were familiar with both the home care assessment and the ICF independently assigned ICF codes to inter-RAI HC items. Subsequently, a series of teleconference meetings were held to reach consensus on the primary code and much later consensus was used to finalize codes for additional items added to the interRAI HC. Results Following exclusion of administrative and diagnostic sections, 175 interRAI items were examined for potential assignment of codes. Of these 52 were assigned codes related to body function, 43 to activities and participation, 34 to environment, 1 to body structure, 17 to not coded, and 26 to not defined. Considering all 3-digit ICF codes, interRAI items addressed 43.2% of Body Function and 50.6% of Activities and Participation codes. Conclusion The conceptual overlap in content, offers an excellent opportunity to operationalize the ICF domains and the codes particularly in the areas of Body Function and Activities and Participation. Use of measures such as the interRAI assessments with common elements across settings facilitates standardized reporting for organizations, regions and nations.